Using Supplemental Lighting to Control Flowering of Hops in Florida - Shinsuke Agehara (EDIS, 2020)
Hops (Humulus lupulus L.) are an emerging crop in Florida. Florida’s craft beer industry has experienced significant growth over the last 10 years, with 285 breweries producing 42.6 million gallons of beer and generating an economic impact of $3.6 billion in 2018. To respond to their strong demand for locally grown hops, an interdisciplinary hops research team is currently studying optimum crop management practices at the UF/IFAS Gulf Coast Research and Education Center (UF/IFAS GCREC). In Florida, the major yield-limiting factor is premature flowering induced by inadequate day length. This new 4-page article, written by Shinsuke Agehara and published by the UF/IFAS Horticultural Sciences Department, provides guidelines for supplemental lighting to control flowering of hops in Florida.